Quality Control on Packing Process of Willarine Margarine Products at PT. XYZ with FMEA and FTA Methods - Ramadhan Argaputra Novantya; Andesta Deny; Hidayat Hidayat (Universitas Islam Raden Rahmat, Malang, 2025)
PT. XYZ is a company engaged in the crude palm oil processing sector, one of which is willarine margarine which is exported to various countries. In maintaining global competitiveness, the company strives to produce high-quality products. However, in practice there are still obstacles that need to be overcome. One of them is during the packing process there are three types of product defects identified, namely leakage in the pouch packaging, lack of margarine volume, and damage to the pouch carton. So this research uses the FMEA (Failure Mode and Effect Analysis) method used to determine and transfer the severity, occurrence, and detection levels, so that it is obtained with the highest total RPN, namely leaky pouch packaging of 904, and FTA (Fault Tree Analysis) as a clue with the root of the problem tree, so that it is known that the root causes are lack of rest time, lack of supervision, no concern for the importance of track setting instructions, and no worker concern for cleanliness. After the results are known, improvement proposals are given, namely providing sufficient rest time and always rechecking, providing track setting instructions, and always doing routine cleaning at the beginning and end of work.